Investigation on emission characteristics of alcohol biodiesel blended diesel engine. Issue 15 (3rd August 2019) - Balan, K. N.; Yashvanth, U.; Booma Devi, P.; Arvind, T.; Nelson, H.; Devarajan, Yuvarajan
ABSTRACT: The present study analyzes the emission pattern of Decanol combined Jatropha biodiesel (JBD100) fueled diesel engine and compared with conventional diesel fuel (D100). Experiments were conducted in a single-cylinder, 4-stroke naturally aspirated diesel engine with an eddy current dynamometer at a constant speed of 1800 rpm. Modified fuel was prepared using a mechanical agitator, in which the Decanol concentration was varied from 10 to 20% to JBD100. The physicochemical properties of Decanol combined biodiesel are within ASTM limits. JBD100 promotes a lower level of carbon monoxide (CO) hydrocarbon (HC), and smoke emissions with notable increases in NOx and carbon dioxide (CO2 ) emissions. An inclusion of 20% Decanol in JBD100 reduces the NOx, Smoke, CO, and HC emission by 7.4%, 4.4%, 5.7%, and 5.9%, respectively, under full brake power.